2013
DOI: 10.1186/1472-684x-12-32
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study examining the sustainability of shared care in the delivery of palliative care services in the community

Abstract: BackgroundThis paper focuses on the sustainability of existing palliative care teams that provide home-based care in a shared care model. For the purposes of this study, following Evashwick and Ory (2003), sustainability is understood and approached as the ability to continue the program over time. Understanding factors that influence the sustainability of teams and ways to mitigate these factors is paramount to improving the longevity and quality of service delivery models of this kind.MethodsUsing qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…While sustainability is widely recognized in the literature, the concept itself is inconsistently defined [26], given the multiple dimension and stakeholders involved [7]. In a very broad way, sustainability is defined as "whether or not something continues to work over time" [27].…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
See 1 more Smart Citation
“…While sustainability is widely recognized in the literature, the concept itself is inconsistently defined [26], given the multiple dimension and stakeholders involved [7]. In a very broad way, sustainability is defined as "whether or not something continues to work over time" [27].…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
“…In a very broad way, sustainability is defined as "whether or not something continues to work over time" [27]. Other approaches are more detailed, with some scholars considering sustainability as addressing the program continuity in its entirety, while others addressed continuity of specific program components [26], improvement of community capacity, programs institutionalisation [19] or the capacity of the program to continuously respond to community issues [28]. These divergent definitions attest that definitional consensus has not been made, and congruent sustainability factors are considered by various scholars or practitioners.…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
“…Taken one step further, the palliative navigator would also be a member of, where available, the palliative care team, which is an interdisciplinary team of practitioners (including social work and spiritual care) that have shown to be particularly effective in rural areas. 7,20 Education, training, and mentorship…”
Section: The Palliative Navigatormentioning
confidence: 99%
“…One of the few studies we found conducted a longitudinal case study by Demiglio and Williams [17] to examine the sustainability of the shared care model among five alternative care teams. Theurer et al studied the mutual support group intervention in long-term care homes and addressed replication and sustainability [18].…”
Section: Literature Reviewmentioning
confidence: 99%